Evaluation of Logistics Management for Basic Immunization Vaccines at the Pharmaceutical Installation, South Sorong District Health Office, Southwest Papua - Pasaribu, Handara Graha; Uly, Nilawati; Al-Maidin, Achmad R. Muttaqien; Zamli, Zamli (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Pharmaceutical services are direct and responsible healthcare services aimed at ensuring optimal therapeutic outcomes and improving patients’ quality of life. Pharmaceutical personnel play a crucial role not only in vaccine production but also in the management of vaccine logistics, including storage, distribution, and administration. Vaccination is estimated to prevent two to three million deaths annually from vaccine-preventable diseases such as diphtheria, tetanus, pertussis, and measles across all age groups. Objective: This study aims to evaluate the management of vaccine logistics at the Pharmaceutical Installation of the South Sorong District Health Office in Southwest Papua, Indonesia. Methods: This research employed a qualitative approach using in-depth interviews with key informants and applied inductive thematic analysis to interpret the data. Results: The findings reveal that although vaccine management practices have been implemented adequately, several challenges remain. These include limited internet connectivity, poor road infrastructure, and logistical delays, all of which hinder the efficiency and effectiveness of vaccine distribution. Conclusion: Strengthening infrastructure and improving digital systems are essential to enhancing the effectiveness of vaccine logistics management. Strategic efforts are needed to overcome these operational barriers to ensure consistent and equitable vaccine availability in remote regions